2017
DOI: 10.1111/fwb.12929
|View full text |Cite
|
Sign up to set email alerts
|

Patterns on a parr: Drivers of long‐term salmon parr length in U.K. and French rivers depend on geographical scale

Abstract: Understanding the geographical scales at which environmental variables affect an individual's body size, and thus their mortality risk, can inform management strategies to help conserve wild populations under climate change. Yet, our current understanding of these relationships is based on studies done at different scales that report inconsistent findings. We predicted that temperature‐related variables (e.g. winter temperature) influence body size at a “regional” scale, that is, affecting individuals in geogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 56 publications
0
19
1
Order By: Relevance
“…The number of days with low discharge was tested against grayling recruitment to capture the effect of low summer discharge rates as an important stressor of the 0+ fish, given that several studies have demonstrated that juvenile salmonid growth and even survival are depressed when summer discharge rates are reduced and vice versa (Davidson, Letcher, & Nislow, 2010;Gregory et al, 2017;Xu, Letcher, & Nislow, 2010). Both Charles et al (2006) and Letcher et al (2015) revealed that survival of 0+ grayling and brook trout survival was reduced during years of low summer discharges and higher water temperatures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of days with low discharge was tested against grayling recruitment to capture the effect of low summer discharge rates as an important stressor of the 0+ fish, given that several studies have demonstrated that juvenile salmonid growth and even survival are depressed when summer discharge rates are reduced and vice versa (Davidson, Letcher, & Nislow, 2010;Gregory et al, 2017;Xu, Letcher, & Nislow, 2010). Both Charles et al (2006) and Letcher et al (2015) revealed that survival of 0+ grayling and brook trout survival was reduced during years of low summer discharges and higher water temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Skoglund, Einum, and Robertsen (2011) revealed salmon eggs incubated at a higher temperature produced larger eggs with higher survival rates versus those incubated at lower temperatures. The general pattern is warmer winters can result in the production of larger juveniles, perhaps due to a more prolonged growth season (Gregory et al, 2017), with these larger individuals then potentially having higher survival rates via greater access to better feeding areas than smaller conspecifics that might be more easily displaced by other foraging salmonids (Huntingford, Metcalfe, Thorpe, Graham, & Adams, 1990). The postincubation temperature anomaly was parameterised as a quadratic effect and had significant and positive effect on postincubation survival up to a threshold of 13.5°C; at higher temperatures, the effect became negative.…”
Section: Discussionmentioning
confidence: 99%
“…There was a significant linear increase in L F over the monitoring period. This could be due to long-term reductions in juvenile density resulting in larger fish (Bohlin et al, 2002;Gregory et al, 2017;Jonsson et al, 1998;Teichert et al, 2011), decadal changes in temperature that result in faster growth of fish (Gurney et al, 2008), or changes in water quality, quantity or food provision that affect fish size (Nislow et al, 2004). In the Girnock Burn, the bias in the estimates of trends in abundance based on the uncalibrated data reflected both the trend in L F (owing to its consequent effect on p) and the trend in p due to unexplained factors (the year effect).…”
Section: Trends In Fork Lengthmentioning
confidence: 99%
“…(It is acknowledged that a management strategy designed to maximize both number and size and condition of smolts would have to account for many complicating factors, such as any negative effect of density dependence on body size.) This could be a particularly pertinent message at present, given evidence that body sizes of juvenile S. salar are decreasing in countries such as England and France (Gregory et al, 2017).…”
mentioning
confidence: 96%